Pedagogical and Professional Competence of English Teachers in EFL Learning at Islamic Senior High School - Nurull Azhar; Aya Maher Tawfik; Aytan Hajiyeva (Journal of Language, Literature, and Educational Research, 2026)
Purpose of the study: This study aims to analyze the pedagogical and professional competencies of English teachers in English as a Foreign Language (EFL) learning at Madrasah Aliyah Madani Alauddin Pao-Pao, Gowa, South Sulawesi, particularly in classroom management, teaching implementation, and mastery of teaching materials. Methodology: This study used a qualitative descriptive method. The subjects were two English teachers at Madrasah Aliyah Madani Alauddin Pao-Pao. Data were collected through classroom observation, structured interviews with teachers, unstructured interviews with students, lesson plan review, and observation checklists. Data were analyzed using the Miles and Huberman interactive model. Main Findings: The findings revealed that pedagogical competence between the two teachers showed significant differences. One teacher was considered less effective due to monotonous teaching methods and limited classroom engagement, while the other teacher was more favored because of interactive teaching strategies. Both teachers demonstrated adequate professional competence in material mastery, technology use, and continuous professional development. Novelty/Originality of this study: This study specifically compares pedagogical and professional competencies of English teachers in an Islamic senior high school context by combining teacher observation and student perceptions. It highlights how student-centered teaching strategies significantly influence teacher effectiveness, providing practical insights for improving EFL teaching quality in madrasah settings.